أحاديثُ أحكام الدِّيانة المجوسيَّة في الكتب الستَّة جمعًا وتخريجًا: A Descriptive and Historical Study of Prophetic Traditions about Mazdaism in the Six Canonical Books of Ḥadīth - العطائي فيصل أحمد ناجي العطائي (الدراسات الإسلامية, 2021)
This study aims to collect and examine Prophetic traditions related to Mazdaism in the six canonical collections of ḥadīth. The Prophet (peace be on him) explained certain matters related to the previous religions, gave detailed rulings about them, and instructed Muslims how to deal with the followers of other religions. The scholars of ḥadīth sciences paid due attention to such ḥadīths and tried their best to distinguish the sound ḥadīth from those of weak and unauthentic ones. The present study defines the concept of Mazdaism, explains who are the followers of Mazdaism, and investigates the places where they lived in the era of the Prophet (peace be on him). Furthermore, it discusses the important issues and differences of scholars about whether Mazdaism is a revealed religion or based on some man-made rituals and doctrines. An inductive and analytical approach has been adopted to collect, study, elaborate, and arrange these traditions of the Prophet (peace be on him).